The Impact of Augmented Reality Based on STEM-Integrated Cognitive Conflict-Based Learning on Student Scientific Literacy, Self-Efficacy, and Retention - Fatni Mufit; Zuhdi Abdilah; Hidayati Hidayati; Selma Riyasni; Zahra Fathanah (Universitas Syiah Kuala, 2025)
This research is motivated by the fact that students have low scientific literacy, self-efficacy, and retention in physics learning, especially on the topics of Newtons law of gravity and Keplers law. This problem is compounded by the use of printed teaching materials that have not been able to develop these three things optimally. Therefore, this study aims to determine the effectiveness and impact of augmented reality (AR)-based teaching materials designed with a STEM-integrated cognitive conflict-based learning (CCBL) in improving scientific literacy, self-efficacy, and student retention. The study employs a quasi-experimental method with a non-equivalent post-test only control group design. The subjects of the study were grade XI phase F students at MAN 1 Padang. The instruments used were scientific literacy tests, self-efficacy questionnaires, and retention tests. Data were analyzed using non-parametric statistical tests in SPSS to determine the differences between the two classes. The results showed that there were significant differences in scientific literacy, self-efficacy, and student retention between the experimental and control classes. Classes using AR learning materials based on STEM-integrated CCBL showed better results compared to control classes. This indicates that the implementation of these learning materials is effective in improving students' abilities in cognitive, affective, and psychomotor abilities. It can therefore be concluded that AR-based STEM-integrated cognitive conflict learning can effectively address the challenges of 21st-century physics education, particularly with regard to improving student scientific literacy, self-efficacy, and retention